2022
DOI: 10.1128/msystems.00091-22
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles of a Foliar Fungal Endophyte ( Pestalotiopsis , Ascomycota) and Its Bacterial Symbiont ( Luteibacter , Gammaproteobacteria ) Reveal Sulfur Exchange and Growth Regulation during Early Phases of Symbiotic Interaction

Abstract: Interactions between microbes and their hosts have important outcomes for host and environmental health. Foliar fungal endophytes that infect healthy plants can harbor facultative endosymbionts called endohyphal bacteria, which can influence the outcome of plant-fungus interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…In a recent dual RNA-seq analysis of EHB Luteibacter sp. cocultured with its host foliar endophyte fungus Pestalotiopsis sp., 11 of 13 of the predicted bacterial T6SS genes were upregulated compared to the axenic free-living bacterial culture [84]. This further supports the hypothesis that T6SS may play a role in the establishment of bacterial-fungal symbiosis relationship.…”
Section: Discussionsupporting
confidence: 73%
“…In a recent dual RNA-seq analysis of EHB Luteibacter sp. cocultured with its host foliar endophyte fungus Pestalotiopsis sp., 11 of 13 of the predicted bacterial T6SS genes were upregulated compared to the axenic free-living bacterial culture [84]. This further supports the hypothesis that T6SS may play a role in the establishment of bacterial-fungal symbiosis relationship.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, one Luteibacter species facilitated the development of barley root and thus might function as plant-beneficial bacteria . Interestingly, Shaffer et al demonstrated that Luteibacter can infect an Ascomycota and alter its functions in auxin and enzyme production Alcanivorax are alkane-degrading bacteria, and their existence in rhizosphere of Calotropis procera was verified to be involved in helping the plant to defend against pathogens …”
Section: Discussionmentioning
confidence: 99%
“…48 Interestingly, Shaffer et al demonstrated that Luteibacter can infect an Ascomycota and alter its functions in auxin and enzyme production. 49 Alcanivorax are alkane-degrading bacteria, 50 and their existence in rhizosphere of Calotropis procera was verified to be involved in helping the plant to defend against pathogens. 51 Nitrosococcus are well-documented ammoniaoxidizing bacteria widely found in wastewater, 52 soil, 53 and rhizosphere, 54 which convert ammonia to nitrate so that it can be utilized by plants.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Adjusted P was estimated by the Benjamini-Hochberg FDR method [ 12 ], and differential enrichment of functional groups of genes was considered significant at P adj < 0.05 [ 38 ]. Several authors consider RNA-seq methods and data analysis approaches to be robust enough such that independent validation by qPCR and/or other approaches is not deemed necessary [ 28 , 86 , 99 , 114 ]. In this study, experimental steps and data analyses were carried out according to the state-of-the-art procedures, and the focus of the study was on modifications of the suites of DEGs rather than on absolute expression levels of single DEGs that can be more precisely characterized by qPCR.…”
Section: Methodsmentioning
confidence: 99%